Negative active material, preparation method thereof and preparation method of negative pole piece

By introducing zirconium tungstate and adding polydopamine-modified carbon fibers into the silicon carbon anode material, the problem of volume expansion of the silicon carbon anode material during the charge and discharge process is solved, and the first charge and discharge efficiency and cycle stability of the battery are improved.

CN119447245APending Publication Date: 2025-02-14JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411578621.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing silicon carbon anode material expands in volume during charging and discharging, resulting in poor cycle stability and low first charge and discharge efficiency.

Method used

By introducing zirconium tungstate into the silicon carbon anode material and baking at high temperature, a zirconium tungstate coated silicon carbon anode material is formed. At the same time, polydopamine-modified carbon fibers and prelithiation treatment are added to improve the lithium embeddedness and cycle stability of the negative electrode material.

Benefits of technology

It effectively suppresses the expansion of silicon-carbon materials, improves the first charge and discharge efficiency and cycle stability of the negative electrode materials, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a negative active material, a preparation method thereof and a preparation method of a negative pole piece, and relates to the technical field of lithium battery processing. The preparation method comprises the following steps: mechanically grinding and mixing a silicon-carbon negative electrode material and zirconium tungstate, baking in a muffle furnace at a high temperature to obtain a negative electrode active material, mixing the negative electrode active material with a binder, a conductive agent, polydopamine modified carbon fiber and carboxymethyl cellulose according to a mass ratio of 85: 10: 5: (1-3): (0.3-0.8), and coating a copper foil with the mixture to prepare a negative electrode piece; wherein the polydopamine modified carbon fiber comprises a silicon-carbon negative electrode material and a plurality of polymers, carbonizing to obtain a porous carbon fiber coated silicon-carbon negative electrode material, and carrying out dopamine deposition to obtain the polydopamine coated carbon fiber. A lithium battery prepared from the negative electrode active material prepared by the invention shows good first charge-discharge efficiency in a test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery processing, and in particular to a negative electrode active material and a preparation method thereof, and a negative electrode sheet preparation method. Background Art

[0002] Nowadays, graphite is mainly used as negative electrode material in the field of new energy batteries. Although graphite has good cycle stability, its low capacity has made it difficult to meet the needs of various industries in an increasingly developed society.

[0003] At present, silicon negative electrode materials have attracted much attention from many scholars due to their high capacity (theoretical gram capacity is 4200mAh / g). Although carbon coating on its surface can alleviate problems such as gas production, structural instability, low initial charge and discharge efficiency, and poor cycle stability, these problems are still urgent. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a negative electrode active material to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a negative electrode active material, the specific steps of which are: grinding and mixing a silicon-carbon negative electrode material and zirconium tungstate, calcining at 250°C-500°C for 6 hours, and cooling to obtain the negative electrode active material; wherein the mass ratio of the silicon-carbon negative electrode material to the zirconium tungstate is (20-30):1.

[0007] Furthermore, a negative electrode sheet made of negative electrode active material includes copper foil and negative electrode slurry coated on the surface of the copper foil; specifically includes the following steps: taking the negative electrode active material, stirring and mixing it with a binder and a conductive agent to obtain a negative electrode slurry; coating the negative electrode slurry on the surface of the copper foil, and vacuum drying it at 120°C for 12 hours to obtain a negative electrode sheet.

[0008] Furthermore, the mass ratio of the negative electrode active material, the binder and the conductive agent in the negative electrode slurry is 85:10:5.

[0009] Furthermore, the preparation method of the negative electrode plate also includes pre-lithiation treatment of the negative electrode plate, and the specific steps include: under a protective atmosphere, dripping 0.1mL-0.3mL of electrolyte on the surface of the negative electrode plate, then covering the metal lithium sheet, applying pressure to short-circuit and fit, and standing for 10min-20min to obtain a pre-lithiation negative electrode plate.

[0010] Furthermore, the negative electrode slurry also includes polydopamine-modified carbon fiber and carboxymethyl cellulose; wherein the preparation steps of the polydopamine-modified carbon fiber are as follows:

[0011] Step 1: Place polymethyl methacrylate in N,N-dimethylformamide and stir for 5h-8h to obtain a polymethyl methacrylate solution; at the same time, dissolve the silicon-carbon negative electrode material in N,N-dimethylformamide, add polyacrylonitrile after ultrasonic dispersion for 1h, stir for 3h-5h, continue to add pyromellitic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide, stir in an ice-water bath for 3h-5h under a nitrogen atmosphere, add the above polymethyl methacrylate solution and mix to obtain a spinning solution;

[0012] Step 2: Take the spinning solution prepared in step 1 and put it into a syringe, spin it to obtain composite fibers, pre-oxidize it under an oxygen atmosphere, introduce a protective atmosphere for carbonization, grind it to obtain modified carbon fibers, soak it in an ethanol solution and then take it out, add Tris buffer and dopamine in turn, oscillate it at 120r / min-150r / min for 6h-8h, let it stand, then wash and dry it to obtain polydopamine modified carbon fibers.

[0013] Among them, the spinning flow rate of step 2 is 0.3mL / h-0.5mL / h, the spinning voltage is 15kV-20kV, the receiving rate is 80r / min-100r / min, and the receiving distance is 10cm-20cm; the composite fiber is pre-oxidized and heated to 250℃-280℃ at a rate of 1℃ / min-3℃ / min for heat treatment for 30min-40min, and naturally cooled to 25℃; carbonization is heated to 600℃-650℃ at a rate of 1℃ / min and then to 1000℃ at 3℃ / min, and kept warm for 30min-40min.

[0014] Furthermore, the mass ratio of the negative electrode active material, the binder, the conductive agent, the polydopamine-modified carbon fiber and the carboxymethyl cellulose in the negative electrode slurry is 85:10:5:(1-3):(0.3-0.8).

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1. The present invention introduces negative thermal expansion material ZrW2O8 into the silicon-carbon negative electrode material, performs high-temperature baking, and obtains a zirconium tungstate-coated silicon-carbon negative electrode; due to the "thermal contraction and cold expansion" of zirconium tungstate, as the internal temperature of the battery rises during the charging and discharging process, the tungsten zirconate material shrinks, which inhibits the expansion of the silicon-carbon material to inhibit the volume expansion of the traditional silicon-carbon negative electrode material during the charging and discharging process, thereby improving the initial charge and discharge efficiency and cycle stability of the negative electrode material;

[0017] 2. The present invention adds a pre-lithiation treatment to the negative electrode plate to improve the lithium insertion capacity of the negative electrode material, compensate for the loss of active lithium in the battery during the first cycle without damaging the cycle stability of the negative electrode material, and improve the first charge and discharge efficiency of the plate;

[0018] 3. The present invention further adds polydopamine-modified carbon fiber, adds silicon-carbon negative electrode material to the polydopamine-modified carbon fiber, and then uses polyimide and polyacrylonitrile as carbon sources, adds pore-forming agent polymethyl methacrylate and blends, and then electrospins the composite fiber, and then pre-oxidizes and carbonizes it to obtain a carbon fiber-loaded carbon-silicon negative electrode material with high specific surface area and high porosity, which provides more active sites and is conducive to the embedding and de-embedding of lithium ions. The deposition of dopamine is used to introduce polydopamine into the carbon fiber, and the strong adhesion and good biocompatibility of polydopamine form a strong adhesion with the electrode components and the copper foil, thereby reducing the shedding of the negative electrode material and improving the cycle stability of the negative electrode material. DETAILED DESCRIPTION

[0019] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0020] In the experiment, the silicon-carbon negative electrode material is SiC; the binder is LA133, the brand is Indile; the conductive agent is Super P, the brand is Swiss Termeco; the battery shell model is CR2032; the thickness of the diaphragm is 20μm, and the diaphragm is made of PE film;

[0021] Preparation of electrolyte: EC and EMC are mixed at a ratio of 3:7, lithium salt LiPF6 is added to obtain a LiPF6 concentration of 1 mol / L, and then 3% FEC is added to obtain the electrolyte;

[0022] Polymethyl methacrylate Mw ~ 35000, polyacrylonitrile MW ~ 50000, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0023] Example 1

[0024] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0025] Example 2: Referring to Example 1, the difference from Example 1 is that the calcination temperature is set to 300°C;

[0026] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 300°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0027] Example 3: Referring to Example 1, the difference from Example 1 is that the calcination temperature is set to 350°C;

[0028] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 350°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0029] Example 4: Referring to Example 1, the difference from Example 1 is that the calcination temperature is set to 450°C;

[0030] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 450°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain a negative electrode active material, which was stirred and mixed with LA133 and Super P at a ratio of active material: LA133: Super P = 85:10:5 to obtain a negative electrode slurry, and heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0031] Example 5: Referring to Example 1, the difference from Example 1 is that the calcination temperature is set to 500°C;

[0032] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 500°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0033] Example 6: Referring to Example 1, the difference from Example 1 is that the mass ratio of SiC to ZrW2O8 is 21:1;

[0034] SiC and zirconium tungstate with a mass ratio of 21:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0035] Example 7: Referring to Example 1, the difference from Example 1 is that the mass ratio of SiC to ZrW2O8 is 23:1;

[0036] SiC and zirconium tungstate with a mass ratio of 23:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0037] Example 8: Referring to Example 1, the difference from Example 1 is that the mass ratio of SiC to ZrW2O8 is 27:1;

[0038] SiC and zirconium tungstate with a mass ratio of 27:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0039] Example 9: Referring to Example 1, the difference from Example 1 is that the mass ratio of SiC to ZrW2O8 is 29:1;

[0040] SiC and zirconium tungstate with a mass ratio of 29:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet.

[0041] Embodiment 10: Pre-lithiation treatment is added on the basis of Embodiment 1;

[0042] Step 1: Grind and mix SiC and zirconium tungstate in a mass ratio of 25:1, transfer to a magnetic boat, place in a muffle furnace for high-temperature baking, calcine at 400°C for 6h at a heating rate of 30°C / min, and cool at an annealing rate of 30°C / min to obtain the negative electrode active material, stir and mix with LA133 and Super P in a mass ratio of 85:10:5 to obtain the negative electrode slurry, and mix at a mass ratio of 120g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet;

[0043] Step 2: Take the negative electrode sheet prepared in step 1, drip 0.3 mL of electrolyte on the surface, cover the metal lithium sheet, apply pressure to short-circuit and fit, let it stand for 20 minutes, and obtain a pre-lithiation negative electrode sheet.

[0044] Example 11: Adding polydopamine-modified carbon fiber and carboxymethyl cellulose on the basis of Example 1;

[0045] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed, transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 hours at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain a negative electrode active material, which was stirred and mixed with LA133, Super P, polydopamine-modified carbon fiber and carboxymethyl cellulose in a mass ratio of 85:10:5:3:0.5 to obtain a negative electrode slurry, coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120°C for 12 hours to obtain a negative electrode sheet;

[0046] The preparation steps of polydopamine modified carbon fiber are as follows:

[0047] Step 1: 2 g of polymethyl methacrylate was placed in 30 mL of N, N-dimethylformamide and stirred for 6 h to obtain a polymethyl methacrylate solution; at the same time, 3 g of SiC was dissolved in 50 mL of N, N-dimethylformamide, and after ultrasonic dispersion for 1 h, 4 g of polyacrylonitrile was added and stirred for 4 h, and then 6 g of pyromellitic anhydride, 6 g of 4,4'-diaminodiphenyl ether and 20 mL of N, N-dimethylformamide were added, and stirred in an ice-water bath under a nitrogen atmosphere for 4 h, and the above polymethyl methacrylate solution was added and mixed to obtain a spinning solution;

[0048] Step 2: Take the spinning solution prepared in step 1 and put it into a syringe, spin to obtain composite fibers, pre-oxidize under an oxygen atmosphere, heat treat at a rate of 1°C / min to 280°C for 30 minutes, and naturally cool to 25°C; then introduce nitrogen for carbonization, heat to 650°C at a rate of 1°C / min and then heat to 1000°C at 3°C / min, and keep warm for 30 minutes; grind to obtain modified carbon fibers, soak them in ethanol solution and take them out, add 30mL of 10mmol / L Tris buffer and dopamine in turn, oscillate at 150r / min for 6 hours, let stand, wash and dry to obtain polydopamine modified carbon fibers.

[0049] The spinning flow rate is 0.5 mL / h, the spinning voltage is 15 kV, the receiving rate is 100 r / min, and the receiving distance is 10 cm; the amount of dopamine used is 0.2 wt% of the modified carbon fiber.

[0050] Example 12: Adding a pre-lithiation step and polydopamine-modified carbon fibers and carboxymethyl cellulose;

[0051] Step 1: Grind and mix SiC and zirconium tungstate in a mass ratio of 25:1, transfer to a magnetic boat, place in a muffle furnace for high-temperature baking, calcine at 400°C for 6 hours at a heating rate of 30°C / min, and cool at an annealing rate of 30°C / min to obtain a negative electrode active material, stir and mix with LA133, Super P, polydopamine-modified carbon fiber and carboxymethyl cellulose in a mass ratio of 85:10:5:3:0.5 to obtain a negative electrode slurry, coat it on a copper foil with a thickness of 11 μm, and vacuum dry it in a vacuum drying oven at 120°C for 12 hours to obtain a negative electrode sheet;

[0052] Step 2: Take the negative electrode sheet prepared in step 1, drip 0.3 mL of electrolyte on the surface, cover the metal lithium sheet, apply pressure to short-circuit and fit, let it stand for 20 minutes, and obtain a pre-lithiation negative electrode sheet.

[0053] The preparation steps of polydopamine modified carbon fiber are as follows:

[0054] Step S1: 2 g of polymethyl methacrylate was placed in 30 mL of N,N-dimethylformamide and stirred for 6 h to obtain a polymethyl methacrylate solution; at the same time, 3 g of SiC was dissolved in 50 mL of N,N-dimethylformamide, and after ultrasonic dispersion for 1 h, 4 g of polyacrylonitrile was added and stirred for 4 h, and then 6 g of pyromellitic anhydride, 6 g of 4,4'-diaminodiphenyl ether and 20 mL of N,N-dimethylformamide were added, and stirred in an ice-water bath under a nitrogen atmosphere for 4 h, and the above polymethyl methacrylate solution was added and mixed to obtain a spinning solution;

[0055] Step S2: The spinning solution prepared in step S1 is loaded into a syringe, and composite fibers are spun to obtain composite fibers. After pre-oxidation in an oxygen atmosphere, the temperature is increased to 280°C at a rate of 1°C / min for heat treatment for 30 minutes, and the fibers are naturally cooled to 25°C; nitrogen is then introduced for carbonization, the temperature is increased to 650°C at a rate of 1°C / min, and then to 1000°C at a rate of 3°C / min, and the temperature is kept for 30 minutes; the modified carbon fibers are obtained by grinding, and the fibers are soaked in an ethanol solution and then taken out, and 30 mL of 10 mmol / L Tris buffer and dopamine are added in sequence, and the fibers are shaken at 150 r / min for 6 hours. The fibers are allowed to stand and then washed and dried to obtain polydopamine-modified carbon fibers.

[0056] The spinning flow rate is 0.5 mL / h, the spinning voltage is 15 kV, the receiving rate is 100 r / min, and the receiving distance is 10 cm; the amount of dopamine used is 0.2 wt% of the modified carbon fiber.

[0057] Comparative Example 1: Comparative Example 1 refers to Example 1, except that there is no calcination step in step 1. The specific steps are as follows:

[0058] SiC and zirconium tungstate with a mass ratio of 25:1 were ground and mixed to obtain the negative electrode active material, and then mixed with LA133 and Super P with a mass ratio of 85:10:5 to obtain the negative electrode slurry. 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet;

[0059] Comparative Example 2: Comparative Example 2 refers to Example 1, except that there is no grinding and mixing step in step 1. The specific steps are as follows:

[0060] SiC and zirconium tungstate with a mass ratio of 25:1 were mixed and transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400°C for 6 h at a heating rate of 30°C / min, and cooled at an annealing rate of 30°C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry. The mixture was heated to 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet;

[0061] Comparative Example 3: Comparative Example 3 refers to Example 1, except that zirconium tungstate is not added. The specific steps are as follows:

[0062] SiC was taken, ground and transferred to a magnetic boat, placed in a muffle furnace for high-temperature baking, calcined at 400 °C for 6 h at a heating rate of 30 °C / min, and cooled at an annealing rate of 30 °C / min to obtain the negative electrode active material, which was stirred and mixed with LA133 and Super P at a mass ratio of 85:10:5 to obtain the negative electrode slurry, and heated at 120 g / cm 2 The coating amount was coated on a copper foil with a thickness of 11 μm, and vacuum dried in a vacuum drying oven at 120° C. for 12 h to obtain a negative electrode sheet;

[0063] Application example: Take the negative electrode sheets prepared in Examples 1-12 and Comparative Examples 1-3, and assemble lithium batteries in a glove box filled with argon according to the assembly sequence of "battery shell - place negative electrode sheets - drip electrolyte - place diaphragm - drip electrolyte - place lithium sheets - place gasket springs - battery shell"; record them as lithium batteries 1-15 according to the sequence of different experimental examples and keep them for future use.

[0064] Detection test

[0065] 1. Use Wuhan Blue Electric CT2001A button battery charge and discharge tester to perform charge and discharge test on lithium batteries 1-15 at 0.2C, with a voltage range of 2.7-4.2V, and record the data.

[0066] 2. Use Wuhan Blue Electric CT2001A button battery charge and discharge tester to perform 50 cycles of 0.2C charge and discharge test on lithium batteries 1-15, with a voltage range of 2.7-4.2V, and record the data.

[0067] serial number First charge and discharge efficiency at 0.2C 50 cycles of charge and discharge efficiency Lithium battery 1 90.2% 80.9% Lithium battery 2 85.3% 76.1% Lithium battery 3 86.2% 76.6% Lithium battery 4 86.8% 77.1% Lithium battery 5 85.9% 76.3% Lithium battery 6 86.1% 75.9% Lithium battery 7 86.9% 77.2% Lithium battery 8 87.5% 77.8% Lithium battery 9 86.7% 75.3% Lithium battery 10 90.7% 81.3% Lithium battery11 90.5% 81.5% Lithium battery 12 91.3% 81.9% Lithium battery 13 83.1% 69.2% Lithium battery 14 84.2% 70.7% Lithium battery 15 84.9% 73.1%

[0068] Conclusion: Based on the above experiments, it can be seen that according to the preparation steps and process parameters of Example 1, the button battery obtained has relatively excellent first charge and discharge efficiency and cycle efficiency in the other examples. The addition of zirconium tungstate effectively improves the cycle life of the battery; Example 10 adds pre-lithiation treatment based on Example 1 to effectively improve the first charge and discharge efficiency of the lithium battery; Example 11 adds polydopamine-modified carbon fiber and carboxymethyl cellulose based on Example 1 to improve the cycle stability of the lithium battery; Example 12 combines Examples 10 and 11 to jointly improve the first charge and discharge efficiency and cycle stability of the lithium battery.

[0069] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode active material, characterized in that: The method comprises the following preparation steps: grinding and mixing silicon-carbon negative electrode material and zirconium tungstate, calcining at 250-500° C. for 6 hours, and obtaining negative electrode active material after cooling.

2. The method for preparing a negative electrode active material according to claim 1, characterized in that: The mass ratio of silicon-carbon negative electrode material to zirconium tungstate is (20-30):

1.

3. A negative electrode active material, characterized in that: The negative electrode active material is prepared by the preparation method according to claim 1.

4. A method for preparing a negative electrode sheet, characterized in that: The method comprises the following steps: taking the negative electrode active material described in claim 3, stirring and mixing it with a binder and a conductive agent to obtain a negative electrode slurry, coating the negative electrode slurry on the surface of a copper foil, and vacuum drying it at 100°C-120°C for 10h-12h to obtain a negative electrode sheet; wherein the mass ratio of the negative electrode active material, the binder and the conductive agent is 85:10:

5.

5. The method for preparing a negative electrode sheet according to claim 4, characterized in that: It also includes pre-lithiation treatment of the negative electrode plate, and the specific steps include: under a protective atmosphere, dripping 0.1mL-0.3mL of electrolyte on the surface of the negative electrode plate, then covering the metal lithium plate, applying pressure to short-circuit and fit, and standing for 10min-20min to obtain a pre-lithiation negative electrode plate.

6. The method for preparing a negative electrode sheet according to claim 4, characterized in that: The negative electrode slurry also includes polydopamine-modified carbon fiber and carboxymethyl cellulose; wherein the preparation steps of the polydopamine-modified carbon fiber are as follows: Step 1: Place polymethyl methacrylate in N,N-dimethylformamide and stir for 5h-8h to obtain a polymethyl methacrylate solution; at the same time, dissolve the silicon-carbon negative electrode material in N,N-dimethylformamide, add polyacrylonitrile after ultrasonic dispersion for 1h, stir for 3h-5h, continue to add pyromellitic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide, stir in an ice-water bath for 3h-5h under a nitrogen atmosphere, add the above polymethyl methacrylate solution and mix to obtain a spinning solution; Step 2: Take the spinning solution prepared in step 1 and put it into a syringe, spin it to obtain composite fibers, pre-oxidize it under an oxygen atmosphere, introduce a protective atmosphere for carbonization, grind it to obtain modified carbon fibers, soak it in an ethanol solution and then take it out, add Tris buffer and dopamine in turn, oscillate it at 120r / min-150r / min for 6h-8h, let it stand, then wash and dry it to obtain polydopamine modified carbon fibers.

7. The method for preparing a negative electrode sheet according to claim 6, characterized in that: In step 2, the spinning flow rate is 0.3 mL / h-0.5 mL / h, the spinning voltage is 15 kV-20 kV, the receiving rate is 80 r / min-100 r / min, and the receiving distance is 10 cm-20 cm.

8. The method for preparing a negative electrode sheet according to claim 6, characterized in that: In step 2, the pre-oxidation is heated to 250-280°C at a rate of 1°C / min-3°C / min, heat treated for 30-40 minutes, and naturally cooled to 25°C; the carbonization is heated to 600-650°C at a rate of 1°C / min and then to 1000°C at a rate of 3°C / min, and kept warm for 30-40 minutes.

9. A negative electrode plate, characterized in that: The negative electrode sheet is prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the negative electrode sheet as claimed in claim 9 in a lithium battery.